Digital Communication in Post Pandemic Times: Impact on Indian Youth - Ashiqha Sultana (Universitas Muhammadiyah Yogyakarta, 2021)
Communication has adapted to various drastic changes during the COVID-19 pandemic. The outbreak of pandemic has forced every form of communication to a complete halt. Connectivity, social-networking, internet advertisements, virtual reality, and video conferencing are no longer optional and have become must-haves. Though COVID-19 is obviously playing a major role as a trigger, the paradigm changes in communication have been emerging throughout. Listening is not easy as before since it has become virtual where some find to balance Indian youth has been greatly affected with the shift taken place during the pandemic and leads the way to the post-pandemic India. The basic question is on how the Indian youth have come across the pandemic times and started looking forward to the new wave in the emerging technological advancements in communication. This research study examines the communication technologies that have emerged mostly during pandemic times and their effect on Indian Youth. The research method used for the study is analytical survey among Indian youth from various Indian cities. The result of the study clearly explains the reception for the communication advancements.